Increasing the Role of Posyandu Cadres in Prevention of Heart Disease in Harjosari Village, Pekanbaru City - Yessi Alza; Ani Laila; Roziana Roziana (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
This activity aims to improve the knowledge and role of Posyandu cadres in Harjosari Village, Pekanbaru City, to prevent heart disease. This activity is carried out as Posyandu cadre training on anthropometric measurements, blood cholesterol examinations, and counseling on healthy eating patterns to prevent heart disease. The activity was conducted at the BRIMOB Posyandu, Harjosari Village, attended by 16 Posyandu cadres. The activity began with anthropometric measurements to determine nutritional status, body fat composition, blood cholesterol examinations, and counseling on healthy eating patterns with the Mediterranean Diet. Mapping the results of anthropometric measurements and blood tests, especially cholesterol levels, shows that most Posyandu cadres are at risk of heart disease. After counseling, the cadres significantly increased their knowledge about heart disease and the Mediterranean diet. Community service activities in Harjosari Village have improved the Posyandu cadres' ability to prevent heart disease. This increase shows the effectiveness of training in strengthening the role of Posyandu cadres in educating the community about a healthy lifestyle and preventing heart disease. There has been an increase in cadres' knowledge about heart disease and the Mediterranean diet so that they are better prepared to educate the community about the importance of a healthy diet to prevent heart disease.